The effect of invalidating the real estate sales contract in accordance with the Jordanian real estate property law - زامل محمد; المساعدة نائل (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The subject of this study relates to the effect of invalidating the real estate sales contract in accordance with the Jordanian Real Estate Property Law, by talking about the two options available to the court in accordance with the text of Article (13) of the Jordanian Real Estate Property Law in the event of an invalid real estate sale contract or an invalid real estate registration transaction, so by talking about the option The first available in Jordanian real estate property law is to restore the situation to what it was before the invalid registration transaction or before the invalid contract. We see that this option is the most appropriate, best, and most appropriate option for practical and realistic application, in addition to achieving the basic goal of the provisions of the law regulating this right. Among them is the stability of real estate transactions. As for the second option, which talks about compensation, we believe that this option, despite being stipulated in Article (13) of the Real Estate Property Law, contradicts the constitutional texts and the general rules governing the rights of the property owner in addition to the provisions of the Civil Procedure Law, as will be talked about in this study.